HYPERTROPHIC CARDIOMYOPATHY, COMPLICATED BIVENTRICULAR HEART FAILURE AND PULMONARY ARTERY THROMBOEMBOLIA, IN AN ELDERLY WOMAN - P. Kh. Dzhanashiya; S. A. Nikolenko; V. A. Nazarenko; L. I. Osmieva; Yu. B. Kunitsky; N. S. Krylova; E. V. Avdeeva (Российский кардиологический журнал, 2010)
The paper presents clinical, instrumental, and pathologo-anatomical data for an elderly female patient with non-obstructive hypertrophic cardiomyopathy (DCMP), complicated by biventricular heart failure, pulmonary artery thromboembolia, and death. The problems of DCMP diagnostics, clinical variants, and possible outcomes are discussed.